Increased left atrial chamber stiffness in hypertrophic cardiomyopathy - Sanada, H; Shimizu, M; Sugihara, N; Shimizu, K; Ino, H; Takeda, R (British Heart Journal, 1993)
OBJECTIVE--To investigate left atrial chamber stiffness and its influence on left atrial and left ventricular functions in hypertrophic cardiomyopathy. DESIGN--Prospective study. SETTING--Department of internal medicine in a university teaching hospital. PATIENTS--Five control subjects, six patients with essential hypertension, and 11 patients with hypertrophic cardiomyopathy. INTERVENTIONS--Measurement of left atrial pressure by a tip micromanometer and of real-time left atrial volume from left atrial cineangiograms. MAIN OUTCOME MEASURE--Left atrial stiffness constant determined by fitting the ascending limb of the v loop of the left atrial pressure-volume relation to an exponential curve. RESULTS--The mean (SD) left atrial chamber stiffness constant was significantly larger in patients with hypertrophic cardiomyopathy than in controls (0.063 (0.018) v 0.041 (0.006), p < 0.05) and was correlated with left ventricular wall thickness (r = 0.560, p < 0.01). Left atrial reservoir volume (left atrial emptying volume before atrial contraction) was significantly smaller in patients with hypertrophic cardiomyopathy than in the controls (7.3 (2.1) v 12.5 (4.4) ml/m2, p < 0.01) and was inversely correlated with the left atrial chamber stiffness constant (r = -0.598, p < 0.01). The cardiac index was inversely correlated with the left atrial chamber stiffness constant (r = -0.542, p < 0.01). CONCLUSIONS--Left atrial chamber stiffness was increased in patients with hypertrophic cardiomyopathy and this affected the left atrial reservoir function. This may in turn have affected cardiac output.